Enzymatic properties of a L-asparaginase without secondary glutaminase activity from Streptomyces scabrisporus - Ricardo Rodríguez-Vargas; Francisca Villanueva-Flores; María Fernanda Gutiérrez-Chávez; Carlos Medrano-Villagómez; Andrés Zárate-Romero; Alejandro Huerta-Saquero (PLoS ONE, 2025)
Acute lymphocytic leukemia (ALL) is characterized by the uncontrolled proliferation of lymphocyte precursor cells within the bone marrow, blood and extramedullary sites. L-asparaginase has become a standard treatment in childhood cases of ALL by reducing the asparagine levels in the bloodstream on which leukemic cells depend, as they cannot synthesize it. The reduction of asparagine leads to cell cycle arrest and death by apoptosis. However, due to the bacterial origin of L-asparaginase, it causes immunogenic reactions, and the cross-glutaminase activity that the enzyme exhibits cause ammonium accumulation and toxicity in different organs and tissues. Enzymes with a lower immunogenic profile that preserve their affinity for the substrate asparagine and that do not have glutaminase activity are needed, such as L-asparaginases from Streptomyces scabrisporus or Rhizobium etli . In this work, the L-asparaginases from S. scabrisporus and R. etli were purified and characterized, and the kinetic parameters of the enzymes were compared under physiological conditions. Furthermore, both enzymes reduced the viability of MOLT-4 leukemic cells in a time- and concentration-dependent manner.